Dr Effects of Adiponectin, Plasma D-Dimer, Inflammation and Tumor Markers on Clinical Characteristics and Prognosis of Patients with Ovarian Cancer: Adiponectin, Plasma D-Dimer, Inflammation and Tumor Markers on Clinical Characteristics and Prognosis of Patients with Ovarian Cancer - Li, Hui (Journal of Medical Biochemistry, 2021)
[Abstract] Objective: To investigate the effects of adiponectin (ADPN), plasma D-dimer (D-D), inflammation and tumor markers on clinical characteristics and prognosis of patients with ovarian cancer. Methods: A total of 80 patients with ovarian cancer treated in our hospital from April 2017 to November 2019 were enrolled as study subjects and evenly divided into observation group (patients with ovarian cancer) and control group (patients with benign ovarian tumor) based on the results of postoperative pathological biopsy. The levels of ADPN, plasma D-D, inflammatory factors and serum tumor markers [carbohydrate antigen 125 (CA125), human epididymis protein 4 (HE4) and risk of ovarian malignancy algorithm (ROMA)] were compared between the two groups. The diagnostic value of serum tumor markers CA125, HE4 and ROMA in ovarian cancer was explored. The correlations of the changes of ROMA with the changes in the levels of ADPN, plasma D-D, high-sensitivity C-reactive protein (hs-CRP), CA125 and HE4 were analyzed. Additionally, the related risk factors affecting the development of ovarian cancer were subjected to univariate and multivariate logistic regression analyses. Results: In comparison with control group, observation group exhibited a lowered ADPN level (p
Keywords: adiponectin, plasma D-dimer, inflammatory factors, tumor markers, ovarian cancer